(untitled) (Boletín Semillero de Investigación en Familia, 2021)
Objective: Determine the presence of burnout syndrome in nursing teachers. Materials and methods: Quantitative, descriptive, cross-sectional study; It was carried out with the teachers of the school of public health of the nursing program of the Universidad de los Llanos, to a total of 60 teachers. For the study, a sociodemographic survey with 9 questions was used, as well as the Maslach Burnout Inventory (MBI) instrument. Results: It was found that men show greater emotional fatigue, teachers have a medium and high level of depersonalization, and regardless of age. Conclusion: The presence of burnout syndrome in teachers is low, being associated with variables such as the female gender, who have good job satisfaction and a better response to coping with stress, having a family and children allows them to develop activities other than work and take active breaks within your working day.